2020
DOI: 10.2174/1570179417666200628140547
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Characterization and Mechanism of Formation of ZnO Nanoparticles Using Petroselinum Crispum Leaf Extract

Abstract: Aims: Synthesizing ZnO NPs using Petroselinum crispum extract, commonly known as parsley, as a source of biosynthesis without utilizing chemical agents for reducing, capping and stabilizing agent. Background: Recently, the biosynthesis of nanoparticles has been widely explored due to the wide range of vital applications in nanotechnology. Biosynthesized zinc oxide nanoparticles, ZnO NPs, has become increasingly important since it has many applications and environmentally friendly. Methods: The innovation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…Due to the easy collection of nutmeg, widespread presence, and also remarkable biological activities, it has become both food and medicine in tropical countries, especially in India and China. , The biosynthesis of zinc oxide nanoparticles was carried out using aqueous fruit extracts of M. fragrans as reducing, capping, and stabilizing agents . Broad studies disclose that volatile oils are the major constituents within the dry biomass of M.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to the easy collection of nutmeg, widespread presence, and also remarkable biological activities, it has become both food and medicine in tropical countries, especially in India and China. , The biosynthesis of zinc oxide nanoparticles was carried out using aqueous fruit extracts of M. fragrans as reducing, capping, and stabilizing agents . Broad studies disclose that volatile oils are the major constituents within the dry biomass of M.…”
Section: Results and Discussionmentioning
confidence: 99%
“…UV-Vis spectroscopy observes this reaction growth. The UV-Vis spectroscopy revealed an absorption peak, associated with the surface plasmon resonance (SPR), gathers conduction band electrons oscillations in responding with electromagnetic waves, demonstrating metal ion reduction and NPs formation [ 51 ]. Parsley leaf extract comprises flavonoids, polyphenols, carotenoids, lipids, polysaccharides, tannins, free organic acids, and essential oils ( Figure 3 ), which are considered essential bio-reducing and stabilizing agents through possessing -OH groups for NPs formation [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our recent works [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] regarding green synthesis nanomaterials, here in this study, an active and easy process of one-pot green synthesis of Ag NPs is proposed. The novelty of this research is that Ag NPs can be formed from a one-pot reaction deprived of employing any exterior stabilizing and reducing agent, which is not conceivable by means of the existing processes.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 3 (a), the EDX analysis of the ZnO thin film indicated that the fabricated ZnO thin film sample contained zinc (Zn), and oxygen (O). The EDX spectrum showed one robust peak for Zn around 1 keV correspondingly and a singular peak for oxygen at ~0.5 keV, which is typical for ZnO thin films [27]. The high intensity of Zn and O peaks displayed that the synthesized thin film sample was mostly ZnO.…”
Section: Resultsmentioning
confidence: 91%